Transarterial Chemoembolization in a Woodchuck Model of Hepatocellular Carcinoma - Pritchard, William F. (J Vasc Interv Radiol, 2020)
PURPOSE: To assess the feasibility of transarterial chemoembolization with drug eluting embolics (DEE) in a woodchuck model of hepatocellular carcinoma (HCC). MATERIALS AND METHODS: Nine woodchucks were studied: 4 normal animals and 5 infected with woodchuck hepatitis virus that had developed HCC. Three animals with HCC underwent multidetector CT (MDCT). A 3F sheath was introduced into the femoral artery and the hepatic arteries were selectively catheterized with 2.0-2.4 F microcatheters. Normal animals underwent diagnostic angiography and bland embolization. Animals with HCC underwent DEE transarterial chemoembolization with 70-150μm radiopaque microspheres loaded with 37.5 mg doxorubicin per ml. Cone-beam CT and MDCT were performed. Following euthanasia, explanted livers underwent microCT, histopathology and fluorescence imaging of doxorubicin. RESULTS: The tumors were hypervascular and supplied by large caliber tortuous vessels with arteriovenous shunts present in two animals. There was heterogeneous enhancement on MDCT with areas of necrosis. Six tumors were identified. The most common location was the right medial lobe (n=3). The mean tumor volume (± SE) was 30.7 cm(3) (± 12.3 cm(3)). DEE chemoembolization of tumors was achieved. Excluding the two animals with arteriovenous shunts, the mean (± SE) volume of DEE injected was 0.49 ± 0.17 ml. Fluorescence imaging showed diffusion of doxorubicin from the DEE into the tumor. CONCLUSION: Woodchuck HCC shares imaging appearances and biological characteristics with human HCC. Selective catheterization and DEE chemoembolization may similarly be performed. Woodchucks may be used to model interventional therapies and possibly characterize radiologic-pathologic correlations.